Analysis of Mental Workload In Remote Graphic Designers In West Java Using The Nasa-TLX Method - Sentosa, Muhammad Aqilla Khalafazka Sentosa; Caesaron, Dino Caesaron; Canny, Susmitha Canny; Daliana, Nadia Daliana (JURNAL TEKNIK INDUSTRI, 2025)
The COVID-19 pandemic has accelerated the adoption of remote work systems, especially in creative industries such as graphic design. While remote work offers flexibility, it also increases mental workload due to multitasking, social isolation, and time pressure. This study aims to evaluate the mental workload of remote graphic designers in West Java, Indonesia, using the NASA-Task Load Index (NASA-TLX) approach combined with cognitive ergonomics. The region has seen significant growth in digital creative employment, making it a relevant case for such an assessment. The method involves six dimensions: mental demand, physical demand, temporal demand, performance, effort, and frustration. Data were collected through online questionnaires and processed using weighting and Weighted Workload (WWL) calculations. Three hundred eight respondents from various cities in West Java participated in this study. Mental demand was the highest workload dimension, with the highest scores predominantly observed among respondents aged 23-30 years and those with 2-4 years of work experience. The results identify key contributing factors to mental workload and analyze its impact on productivity and worker well-being. We recommend two cognitive ergonomics-based interventions, such as Task Chunking and Goal Setting Theory, that must be tested and validated for their effectiveness in reducing workload levels. The findings support the development of structured strategies to manage mental workload in remote digital environments, particularly in emerging creative hubs like West Java.